2021
DOI: 10.1017/s1478951521000110
|View full text |Cite
|
Sign up to set email alerts
|

Equal palliative care for foreign-born patients: A national quality register study

Abstract: Objectives To use data from a national quality register to investigate if there are differences relating to migrant background in the quality of end-of-life care of patients dying in Sweden. Methods A retrospective, comparative register-based study. In total, 81,418 deceased patients, over 18 years of age, registered in the Swedish Register of Palliative Care during 2017 and 2018, of expected death were included in the study. Of these, 72,012 were Swedish-born and 9,395 were foreign-born… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The findings from this study might reflect barriers (including infrastructure and competency) or different preferences regarding place of death – or even differences in terms of access to specialist palliative care since both Swedish and international studies indicate that foreign-born individuals and ethnic minorities are less likely to be cared for within specialized palliative care. 19 , 26 , 44 , 45 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings from this study might reflect barriers (including infrastructure and competency) or different preferences regarding place of death – or even differences in terms of access to specialist palliative care since both Swedish and international studies indicate that foreign-born individuals and ethnic minorities are less likely to be cared for within specialized palliative care. 19 , 26 , 44 , 45 …”
Section: Discussionmentioning
confidence: 99%
“… 25 A German study shows that immigrants are underrepresented in Hospice and Palliative Care (HPC), foremost Turkish immigrants 19 and a study conducted in Sweden shows that foreign-born individuals are less likely of being cared for in specialized palliative care units. 26 Thus, there is a need for population-based studies to ensure that palliative care needs are met in whole populations, including people who have immigrated. Investigating place of death and associated factors in a population is a way of learning about and understanding patterns and inequalities regarding access to and utilization of healthcare services.…”
Section: Introductionmentioning
confidence: 99%
“…These studies demonstrate that communication can be a barrier to health literacy in relation to palliative and EOL care which can lead to limited access to services. While the studies identified above found communication and culture as barriers to accessing palliative and EOL care, one study (Carlsson & Hjelm, 2021) only reported on the difference in access to palliative care between Swedish-born patients and foreign-born, reporting that the Swedish-born patients accessed the services more than the foreign-born. The reason for not providing more information on the access ratios between the two population was because the study was conducted using deceased patients’ registers.…”
Section: Culture and Communication Barriersmentioning
confidence: 99%